Stature Estimation from Foramen Magnum Region in Chinese Population1. Issue 5 (23rd July 2013) - Cui, Yaming; Zhang, Jizong
Abstract: Estimation of stature from body parts plays a vital role in identifying the dead. This study focused on dimensions of the foramen magnum region and examined the relationship between stature and the dimensions of the foramen magnum region in northern and southern Chinese populations. Measurements were taken on the skulls of 276 individuals (all male). Data on 48 individuals from northern China and 140 from southern China were used for further stature reconstruction of the above two populations in China. Statistical analyses indicate that bilateral variation is insignificant for all measurements except maximum length of condyle in the southern Chinese population ( p < 0.01) and that the northern and southern populations differ significantly only in the minimum distance between condyles. Linear and multiple regression equations for stature estimation were established. The correlation coefficients between stature and the various measurements differed between the northern and southern Chinese populations.